Maternal Transmission of SARS-CoV-2: Safety of Breastfeeding in Infants Born to Infected Mothers - Al-kuraishy, Hayder M.; Al-Gareeb, Ali I.; Atanu, Francis O.; EL-Zamkan, Mona A.; Diab, Hassan M.; Ahmed, Ahmed S.; Al-Maiahy, Thabat J.; Obaidullah, Ahmad J.; Alshehri, Sultan; Ghoniem, Mohammed M.; Batiha, Gaber E. (Frontiers in Pediatrics, 2021)
Epidemics and spread of infectious diseases has serious impact on the provision of nutrition and care services for newborns and has significantly impacted all patient including pregnant mothers and their newborns. As pregnancy affects the physiological and immunological functions and thus changes the vulnerability of pregnant women to infection, pregnant women constitute an extremely vulnerable, community. The entire planet is now threatened by the pandemic of SARS-CoV-2 (COVID 19) infections which is considered a new public health crisis due to its rapid spread. The outcomes of epidemic coronavirus disease (COVID-19) and its impact on pregnant women and their new-borns is addressed comprehensively in this review, as well as the recommendations for the management of pregnant and newborn patients in the event of this pandemic.